Green manuring and other form of soil improvement in the Tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
'Green manuring and other forms of soil improvement in the Tropics', Agrodok 28, 47pp. ISBN 90 7274616 3